COMPARISON OF CLINICAL COURSE AND TREATMENT COMMUNITY-ACQUIRED PNEUMONIA OF CONSCRIPT SOLDIERS FROM 1989 TO 2012 - Попенко, Н.В. (World of Medicine and Biology, 2015)
The article analyzes the characteristics of the course, the spectrum of pathogens and assess the effectiveness of treatment of community-acquired pneumonia of conscript soldiers. Analyzed the medical history of 251 conscripts soldiers aged 17 to 24 years who were ill with community acquired-pneumonia, including mild course was observed in 72 (28.68%), moderate severity - in 86 (34.26%), and severe pneumonia - 93 (37.05%).Patients with community-acquired pneumonia were divided into three groups. The first included 84 conscript soldiers that were sick with community- acquired pneumonia during the 1989 - 1996 years. The second group included 83 conscripts soldiers who have had community-acquired pneumonia during 1997 - 2004, the third group - 84 soldiers, treated from 2005 to 2012. The most frequently observed severe course occured in the third group of concript soldier patients (2005 - 2012) - 58.33%.Most important for the development community-acquired pneumonia from 1989 to 2012 had acute rhinosinusitis - 23 (9.16%).Overwhelming etiologic significance Str. pneumoniae and S. aureus by community-acquired pneumonia of concript soldiers was found and taken into account in the appointment of empirical antibiotic treatment. Detection of H. influenzae increased from the (3,45 ± 1,69)% in 1997-2004 to (8,0 ± 2,42)% in 2005-2012.In the second group of patients should be noted leading role in the occurrence of pneumonia family Gram-negative bacteria Neisseria 13 (11,2 ± 2,93)%, which were almost absent in the first group of patients 1 (1,05 ± 1,04)% and were found in the middle number of patients in the third group 7 (5,6 ± 2,05)%.It is noted significant increase with age among pathogens causing mixed infection in the first group of patients conscripts soldiers - 22 (13,67 ± 27)% of microorganisms in the second - 62 (38,5 ± 3,83)%, in the third - 77 (47,83 ± 3,94)% of microorganisms. Agents that form mixed infection is Streptococcus 60 members of the family (37,27 ± 3,8)% and Staphylococcus 59 (36,65 ± 3,79)%, Neisseria 18 (11,18 ± 2,48)% and H. influensae 8 (4,96 ± 1,7)%.Regional characteristics sensitivity Str. pneumoniae to antibiotics, namely, decreased sensitivity to penicillin and its increase to protected clavulanic acid penicillins, macrolides, and fluoroquinolones have been established for recent years. That allows us to recommend to use these antibiotics for treatment of community-acquired pneumonia of young persons who are a part of an organized group.
Keywords: community-acquired pneumonia; diagnostics; conscript soldiers; antibiotic therapy